2021
DOI: 10.24090/tarling.v5i1.4984
|View full text |Cite
|
Sign up to set email alerts
|

Need Analysis on Writing Skill: What Do The Students Really Need for Writing Course?

Abstract: This study aims to investigate the needs of students in writing skills. In particular, this research attempts to explore the present situation, the target, and the learning needs for the writing course. Need analysis is conducted for deciding the goals and the objectives of the upcoming curriculum and for ensuring that the curriculum content ties the students’ needs. A descriptive method was employed in this study. A questionnaire was used for collecting the data which then analyzed and described qualitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The target situation analysis is related to the roles of students and their language abilities as well as the level of understanding necessary for writing analytical exposition text. The questionnaire was adopted from Sabarun (2019), andMa'rufah et al (2021) and consisted of two parts.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The target situation analysis is related to the roles of students and their language abilities as well as the level of understanding necessary for writing analytical exposition text. The questionnaire was adopted from Sabarun (2019), andMa'rufah et al (2021) and consisted of two parts.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, needs analysis can also serve as a means of identifying the challenges that students face during the process of learning, as well as their perspectives on the dynamics of learning and teaching within the classroom setting (Richards, 2015). Several studies have demonstrated the advantages of employing needs analysis in the writing classroom, particularly within the Indonesian context (Ilham et al, 2020;Ma'rufah et al, 2021;Sabarun, 2019;Sakkir et al, 2021). However, it is worth noting that although past research has highlighted the benefits of needs analysis, these studies have primarily concentrated on the use of needs analysis inside university settings, with a specific emphasis on enhancing the general writing skills of undergraduate students.…”
Section: Introductionmentioning
confidence: 99%
“…However, many students have limited opportunities to acquire proficient writing skills. A study by Ma'rufah, Muflihah and Awaliyah (2021) showed that most new students at the English Education Department of the State Islamic Institute of Purwokerto demonstrated limited, poor abilities when it comes to their writing skills. This could be attributed to the lack of training in writing before entering college (Keong & Mussa, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A number of research studies show that need analysis helps teachers prepare materials appropriately (Albashir Jamoom, 2021;Ilham et al, 2020;Ma'rufah et al, 2021;Padmadewi et al, 2023;Sakkir et al, 2021). Sakkir (2021), for example, the study found that need analysis is the basis of developing a module for Facebook-based writing instructional courses, in order to make the material related to students' needs.…”
Section: Introductionmentioning
confidence: 99%